(untitled) (Research, Society and Development, 2022)
Objective: to investigate the scientific evidence in the literature on the effects of Ascorbic Acid on biochemical outcomes such as hemoglobin, ferritin, and transferrin saturation in patients with chronic kidney disease undergoing renal replacement therapy. Methods: This is an integrative literature review study with a qualitative approach. Databases were used; Latin American Literature in Health Sciences (LILACS), Medical Literature and Retrieval System online (Medline), Excerpta Médica dataBASE (EMBASE), Cochrane Library. Eleven studies were included, only clinical trials that used ascorbic acid in hemodialysis patients and analyzed its effects. Results: The findings corroborate the efficacy of Ascorbic Acid as an adjuvant in the treatment of anemia in patients undergoing hemodialysis treatment, since it increases serum hemoglobin and reduces the need for Human Recombinant Erythropoietin. In addition, they depict a reduction in serum ferritin levels and an increase in transferrin saturation, a fact that increases its bioavailability and is useful in functional iron deficiency. Conclusion: Although studies are limited by the small number of participants, short duration of follow-up after the intervention and quality variability, Ascorbic Acid appears to be effective as an adjunct in the control of anemia. Longer-term studies are needed to confirm these results, report adverse events, and determine the impact on long-term outcomes.